An Economic Analysis of Security Policies - Tilman Brück (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper analyses public policy choices in the security economy from an economic perspective. It discusses the role of public goods for national and global security and identifies the importance of the first- and second-order indirect effects of insecurity on economic activity, which include the behavioural responses of agents and the government to security measures, akin to such effects in insurance economics. Furthermore, key public policy trade-offs are outlined, in particular between security and efficiency, globalisation, equity and freedom. The analysis identifies suitable policy options for raising security in the national and international contexts and in view of these trade-offs. A suitable balance between market and non-market instruments in achieving security should be aimed for to minimise the adverse effects of aiming for higher security. In addition, the public good nature of security implies that international coordination of security policies is important, despite this process being itself fraught with enforcement problems.
Keywords: H40; K40; D74; 330; collective goods; public policy; regulation; risk; security; terrorism